Communication Strategy of the Provincial Government of North Sumatra Through Instagram Accounts @pemprovsumut in Increasing the Positive Image of the Provincial Government of North Sumatra - Wahyu Ramadhan; Iskandar Zulkarnain; Humaizi (Journal of Social Interactions and Humanities, 2023)
The purpose of this study was to find out how the communication strategy implemented by the Provincial Government of North Sumatra in forming a positive image through Instagram social media @pemprovsumut and the obstacles encountered in carrying out this communication strategy. This study uses the constructivism paradigm with a qualitative descriptive approach. Data collection techniques were carried out through in-depth interviews, non-participatory observation, and document/library study collection. An important finding of this study is that the North Sumatra Province Communication and Information Service has carried out a communication strategy that includes (1) Establishing communicators, (2) Establishing targets, (3) Establishing work teams, (4) Establishing message delivery mechanisms, ( 5) Dissemination of communication media, and (6) preparation of an activity schedule (schedule). The six strategies are efforts to increase a positive image in society. However, the communication strategy implemented by the North Sumatra Province Communication and Information Service is still not effective enough to enhance a positive image. Some of the problems faced are budget constraints, professionalism and limited human resources, the function of the e-Government Service Division as manager of the @pemprovsumut Instagram admin which is not yet optimal, the competence of the leadership and members in understanding communication on social media is not yet good, and the lack of coordination and synergy between the e-Government Service Sector and the Public Information Management Sector in terms of providing up to date information.